ACARYA'S EDUCATIONAL COMMUNICATION SERVES AS A LEARNING STRATEGY TO PROMOTE RELIGIOUS MODERATION AT PASRAMAN SAD DHARMA DWIJENDRA IN MATARAM - Andari, Ida Ayu Made Yuni; Wiguna, Ida Bagus Alit Arta (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2025)
Hindu religious education through pasraman plays an important role in the formation of the religious character and nationality of the younger generation in Indonesia. In the context of a multicultural society, educational communication carried out by an Acarya is a crucial strategy in instilling religious moderation values such as tolerance, love for the homeland, anti-violence, and respect for cultural diversity. This study aims to analyze the form and role of Acarya educational communication in learning the value of religious moderation in Pasraman Sad Dharma Dwijendra Mataram. We collected data using a descriptive qualitative approach, which involved in-depth interviews, participatory observations, and documentation of learning activities and interactions between Acarya and Sisya. The results of the study show that Acarya educational communication includes an exemplary approach, interactive dialogue (Dharma Tula), and the delivery of Hindu narratives that are contextualized with social realities. These findings indicate that communication is not only a means of delivering material but also a medium for value transformation. This article contributes to the development of a religious learning model that is adaptive and relevant to the context of Indonesia's diversity. The results of this study are important to strengthen inclusive and transformative Hindu educational practices during complex socio-religious dynamics.